2015
DOI: 10.1016/j.neuron.2015.02.025
|View full text |Cite|
|
Sign up to set email alerts
|

A Genome-wide Screen Identifies PAPP-AA-Mediated IGFR Signaling as a Novel Regulator of Habituation Learning

Abstract: Summary Habituation represents a fundamental form of learning, yet the underlying molecular genetic mechanisms are not well defined. Here we report on a genome-wide genetic screen, coupled with whole genome sequencing, that identified 14 zebrafish startle habituation mutants including mutants of the vertebrate specific gene pregnancy associated plasma protein-aa (pappaa). PAPP-AA encodes an extracellular metalloprotease known to increase IGF bioavailability thereby enhancing IGF receptor signaling. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 102 publications
9
104
0
Order By: Relevance
“…In fact, we found that differences in the rate of habituation between individuals are maintained over days and are heritable, indicating that ASR habituation has a genetic or epigenetic component. The genetic implications are consistent with recent findings from a forward genetic screen in larval zebrafish, which identified several mutants that affect ASR habituation without affecting startle performance (Wolman et al, 2015). Two of these genes were identified: one encoding the metabolic enzyme pyruvate carboxylase and the other the pregnancy-associated plasma protein A, a secreted metalloprotease.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, we found that differences in the rate of habituation between individuals are maintained over days and are heritable, indicating that ASR habituation has a genetic or epigenetic component. The genetic implications are consistent with recent findings from a forward genetic screen in larval zebrafish, which identified several mutants that affect ASR habituation without affecting startle performance (Wolman et al, 2015). Two of these genes were identified: one encoding the metabolic enzyme pyruvate carboxylase and the other the pregnancy-associated plasma protein A, a secreted metalloprotease.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, these data suggest increased habituation or non-associative learning in AB over TL larvae. A recent study in zebrafish larvae showed that IGF1 increases acoustic startle habituation through activation of the IGF1 receptor thereby regulating synaptic strength [40], in line with the proposed role of IGF1 in neuronal plasticity [29]. Hence, we hypothesise here that the difference in habituation between AB and TL may be related to higher levels of expression of igf1 , that we observed in AB compared to TL larvae.…”
Section: Discussionsupporting
confidence: 80%
“…More recently, a forward genetic screen provided interesting insights into habituation learning [66]. However, such an approach for the study of sleep presents several challenges.…”
Section: New Approaches and Genetic Pathwaysmentioning
confidence: 99%